A new species of Zaglyptogastra Ashmead, 1900 (Hymenoptera: Braconidae: Braconinae) from Vietnam - Long, Khuat Dang; Mai, Pham Quynh (Zootaxa, 2015)
The moderately large genus Zaglyptogastra Ashmead, 1900 is newly recorded for Vietnam and one new species, Z. vietnamica Long sp. n., is described and illustrated. Differences between the new species and two described species, Z. aswada El-Heneidy & Quicke, 2007, from Indonesia (Sumatra) and Z. vitalisi (Turner, 1919), from Laos, are given.